Kwesta i kwiaty. Opozycyjne obrazy przestrzeni w „Malwinie” Marii Wirtemberskiej - Norkowska, Aleksandra (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article examines symmetry as a method of constructing the world in Maria Wirtemberska’s Malwina, that is, The Perspicacity of the Heart. The author draws particular attention to the opposing textual and semantic structures in the chapter entitled “Charity”. The focus is on contrasting images of vita activa and vita contemplativa, drawing the reader’s attention to reflections on humanist philanthropy and the Christian concept of charity. This topic is situated against the backdrop of pre-Romantic ideas that underpinned the creation of a sublime way of experiencing the world by the titular protagonist of this late Enlightenment work.